Antioxidant effect of Lonicera Caerulea on heat stress-treated male mice - Donghun Kang; Daeyoung Kim (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Lonicera caerulea (Honey berry, HB) has been used in medical treatment in Russia, Japan, China and Korea. It has high level of vitamin C and polyphenolics. Polyphenolics can improve anti-inflammatory effect and prevent cancer, diabetes mellitus type 2. Also, Vitamin C is a representative anti-oxidant. however, it is still unknown what effect it will have on the oxidation stress of the reproductive system. In previous studies, ROS can be produced when it is exposed to heat stress and has negative effect on sperm's maturation, capacitation, hyperactivation, acrosome reaction and fusion of egg and sperm. Therefore, the purpose of this study is to investigate the antioxidant effects of L. Caerulea on the sperm and mice. At first, it conducted using ICR mouse (n = 20) for 4 weeks. There are four groups of mice (n = 5 per group). Also, L. Caerulea was taken by oral gavage. Group I (control) kept at 23℃-27℃ and administer D.W (0.5 mL/day), Likewise, Group II (HB) kept at room temperature but gave HB (250 mg/kg, 0.5 mL/day), Group III (HB + HS) received heat stress (40℃) using hyperthermia induction chamber and gave HB at same dose. and Group IV (HS) exposed heat stress only. Mainly, we showed degree of gene expression using Western blot in SOD, HSP 70, 17β-HSD and Real-time PCR. It can find correlation between intracellular activity like steroid hormone, apoptosis under ROS and antioxidant activity of L. Caerulea.